Temporal-Spatial Transcriptome Analyses Provide Insights into the Development of Petaloid Androecium in Canna indica - Tian, Xueyi; Yu, Qianxia; Liu, Huanfang; Liao, Jingping (Frontiers in Plant Science, 2016)
Canna indica (Zingiberales) is one of the most important ornamental species characterized with beautiful petaloid staminodes, which are considered to evolve from stamens. However, the genetic basis for the development of petaloid staminodes remains unclear largely because the genomic sequences are not available. By using RNA-Seq, we sequenced the transcripts in the flower of Canna indica, and quantified the temporal gene expressions in flower primordium and differentiated flower, as well as the spatial gene expressions in petal and petaloid staminode. In total, 118,869 unigenes were assembled, among which 67,299 unigenes were annotated. Quantification analysis identified the differentially expressed genes in the temporal and spatial two comparisons, based on which, Gene Ontology enrichment analysis highlighted the representative terms in each sample, such as specification of organ number in flower primordium, growth in differentiated flower, secondary cell wall biogenesis in petal and cell division in petaloid staminode. Among the 51 analyzed MADS-box unigenes, 37 were up-regulated in differentiated flower compared with those in flower primordium. A-class unigenes were expressed higher in petal than in petaloid staminode, and C-class unigenes were expressed oppositely, whereas B-class unigenes demonstrated close expression levels in these two organs, indicating that petaloid staminode retains stamen identity to some degree. In situ hybridization provided more detailed expression patterns of these unigenes, and revealed the extended expression of B-class to the carpel at later stages when the style turned flat. These results constitute a preliminary basis for the study of flower development in Canna indica and can be applied in further study of the evolution of Zingiberales.